The Study of Identity Related with Evolutionary Revolution in the Writings by Manuel González Prada - Sevilla-Vallejo, Santiago (2021)
The formation of the identity of collectives is essential for the understanding of their history. Manuel González Prada is one of the most important authors in the definition of Peruvian identity. He denounced the identity composed of prejudices, atavistic fears and submission to the authority inherited from Spanish rule and worked to build a social identity based on science, rebellion and freedom. In this paper, we study the construction of identity made by the author from the narrative model of Paul Ricoeur and the change of the cultural logic defined by Jean Pierre Olivier de Sardan. For this purpose, the following texts are analyzed:Páginas libres (1894), Horas de lucha (1908), Bajo el oprobio (1933) and Anarquía (1946). In these works, Manuel González Prada criticizes the identity of domination that prevailed in Peruvian society, whereby one group imposes itself on another group, which responds with humility and resignation. Therefore, he urges a change in the collective identity, characterized by a critical sense, that is, he promotes a social attitude of pride and rebellion against the abuses of power. Thus, the revolution proposed by Manuel González Prada would lead to a change in the Ricoeurian ipseidad and to the rupture of a cultural logic of corruption.